Implementation of chatbot in online commerce, and open innovation - Illescas-Manzano, María D.; López, Noé Vicente; González, Nuno Afonso; Cristófol Rodríguez, Carmen (MDPI AG, 2022)
This study describes the chatbot journey and focuses on its implementation within the digital marketing strategy in the first part of a company’s sales funnel. The main goal was to apply a chatbot via Facebook Messenger supported by the ManyChat platform to increase the number of leads, comparing the chatbot with the previous strategy used by the company to obtain contact information. This research work takes a step further and shows that implementing a chatbot through the ManyChat platform by a company that markets online has a positive impact on the capturing of leads, as opposed to the results obtained by authors such as Luo et al. and Leung et al. A chatbot platform used with the intention of obtaining leads seems to be an agile and powerful tool; in fact; the main conclusion of this work is that including this method can be one of the main axes of obtaining information about consumers with the aim of performing marketing actions in a two-way communication that facilitates sales by companies.
Keywords: chatbot; consumer perception; digital communication; digital marketing; facebook; flow; funnel; lead; lead magnet; manychat; messenger; Scopus